%3D%20%20-%20%28x%20-%203%29%20%2B%204%20" id="TexFormula1" title=" \frac{1}{2}(2 - 6x) - 4(x + \frac{3}{2}) = - (x - 3) + 4 " alt=" \frac{1}{2}(2 - 6x) - 4(x + \frac{3}{2}) = - (x - 3) + 4 " align="absmiddle" class="latex-formula">
1 answer:
Answer:
x=-2
Step-by-step explanation:
1/2(2-6x)-4(x+3/2)=-(x-3)+4
(1-3x)-4x-6=-x+3+4
-7x-5=-x+7
Tranpose
-7x+x=5+7
-6x=12
Divide by -6
x=-2
You might be interested in
Answer:6908 (miles) ^2
Step-by-step explanation:
diameter=2200 miles
π=3.14
Circumference=π x diameter
Circumference=3.14 x 2200
Circumference=6908 (miles)^2
Answer: 2/4 is less than 2/3
The answer is C. 4x^5 + 3 + 2/x^5
D.
X+3
I attached a picture
Answer:
John Adams
Step-by-step explanation:
He was the 2nd President in the USA.